An application of the GMM model on economic growth in Indonesia - Yunidar Purnama Sari, Aliasuddin, Eddy Gunawan, (Opción, 2019)
This study empirically examines the effects of money supply, exports, and interest rates on economic growth in Indonesia via a Generalized Method of Moment (GMM) model. As a result, the use of Instrumental Variables (IV) is valid for the model and that all variables have a significant effect, with a one percent significance level. Money supply and exports have a positive effect on economic growth and interest rates have a negative effect on economic growth. In conclusion, the implementation of an effective monetary policy, one that uses interest rates well, is necessary to maintain the stability of the money supply.